Isolated Scalp Nodule in Patient with Undiagnosed RCC. (2006) - Pan, David; Niall, Owen; Sharma, Harbinder; Gya, Devan
Abstract : An unexpected diagnosis of metastatic RCC after excision biopsy of a skin nodule can bring uncertainty. A case of isolated scalp metastasis from undiagnosed RCC was noted and a review of the literature was undertaken to aid management. RCCs often present with distant disease involving multiple organ systems. Single metastasis to the scalp region without other organ involvement is uncommon. Cytoreductive nephrectomy and limited metastectomy offer survival advantage in physically fit patients with RCC.